GHRH-GH-IGF1 axis in pediatric Down syndrome: A systematic review and mini meta-analysis - David Shaki; David Shaki; Eli Hershkovitz; Eli Hershkovitz; Shai Tamam; Arkadi Bollotin; Odeya David; Odeya David; Guy Yalovitsky; Neta Loewenthal; Neta Loewenthal; Lior Carmon; et al. (Frontiers Media S.A., 2023)
ObjectiveTo analyze and determine the quality of functioning in different components of GHRH-GH-IGF1 axis in children with Down syndrome (DS).DesignSystematic review and mini meta-analysis of the literature.MethodsA search was performed in PubMed, Embase, Scopus, and PsycINFO through August 2022. Eligible studies included pediatric patients with DS who had undergone any laboratory evaluation of the GHRH-GH-IGF1 axis. Two reviewers independently screened articles for eligibility. Results of each type of test were weighed together in patients both with and without DS and were pooled using a random effects meta-analysis.ResultsIn total, 20 studies assessed the GHRH-GH-IGF1 axis function. A defect in three major components of GHRH-GH-IGF1 axis was found in a significant proportion of pediatric DS patients.ConclusionsA significant portion of short-stature pathogenesis in children with DS is associated with impaired GHRH-GH-IGF1 axis function.